Study on Mechanical and Ecological Properties of Fly Ash Substrate for Ecological Slope Protection - Juan Wan; Jun Zhu; Henglin Xiao; Qiang Ma (Advances in Civil Engineering)
In order to realize the resource utilization of fly ash, a kind of ecological slope protection substrate was prepared by mixing fly ash produced by MSW incineration into slope protection soil. Through the direct shear test and a leaching experiment on ion pollutants, the influence that shear strength of the substrate changed with root content, ash content, and moisture content and the ecological effects of leach liquor were investigated. The results showed the following: (1) When the optimum moisture content is about 24.9%, the shear strength of the substrate is the maximum. (2) Fly ash can improve the shear strength of the soil, which can reach 1.67 times as much as that of plain soil, and the optimum content of fly ash is 5%–6.7%. (3) The root system can increase the cohesion and internal friction angle of the substrate soil but mainly increases the cohesion of the substrate soil. (4) Plants grow taller in ash-mixed soil than in plain soil. (5) When the fly ash content is 20%, the ion concentrations of Cl, Cu, and Zn are the highest: 220.7, 0.153, and 1.526 mg/L, respectively. All of them are lower than the standard limit of class V water and gradually decrease with time. Therefore, the leaching liquid will not cause environmental pollution and meet the ecological requirements.